Molecular identification and phylogenetic relationship of Bangladeshi pufferfish based on mitochondrial COI and 16S rRNA genes - Md Sagir Ahmed; Nafisa Islam; Durjoy Raha Antu; Mysha Mahjabin; Sujan Kumar Datta; Osamu Arakawa (Journal of Agriculture and Food Research)
Pufferfish is common in marine, brackish and freshwater habitats in Bangladesh. Pufferfish poisoning sporadically occurs due to the consumption of toxic pufferfish throughout the country. Identification of pufferfish is challenging and/or misleading, based on only morphometric characteristics. A study was conducted for molecular characterization and phylogenetic analysis of Bangladeshi pufferfish using two markers, mitochondrial cytochrome c oxidase I (COI) and 16S ribosomal RNA (16S rRNA) genes. We aimed to generate DNA barcode sequences of pufferfish in Bangladesh waters, explore the differences and applicability of two gene fragments (16S rRNA and COI) in fish species identification, and establish a comprehensive barcoding reference database for pufferfish. A total of 36 barcode sequences (20 sequences of COI and 16 sequences of 16S rRNA) were obtained from 33 collected specimens representing seven species and five genera. The mean length of the sequences was 644 bp and 613 bp for COI and 16S, respectively. The average %GC content was 49.96 for COI which was higher compared to the 16S rRNA (46.30). The average Kimura two parameter (K2P) distances within species were found to be 0.29 ± 0.01 for COI and 0.70 ± 0.06 for 16S rRNA. The Neighbor-Joining (NJ) phylogenetic analysis of COI and 16S rRNA gene sequences revealed that the corresponding species were clustered together in the same clade. Results of cluster sequence analyses revealed seven Operational Taxonomic Units (OTUs). This study validates the utility of both COI and 16S rRNA as potential markers for identifying different puffer species. DNA-based identification of the remaining pufferfish species of Bangladesh, with multiple sequences and phylogenetic relationships remains to be established.